Experimental Assessment of a Skyhook Semiactive Strategy for Seismic Vibration Control of a Steel Structure. (22nd February 2018) - Caterino, Nicola; Spizzuoco, Mariacristina; Occhiuzzi, Antonio; Bonati, Antonio
Abstract : Sky-hook damping is one of the most promising techniques for feedback control of structural vibrations. It is based on the idea of connecting the structure to an ideal fixed point of the space through passive dissipative devices. Herein the benefit of semiactive (SA) sky-hook (SH) damping is investigated for seismic protection of a two-storey steel frame via shaking table tests. This kind of SA control is achieved implementing a continuous monitoring of selected structural response parameters and using variable dampers. The damping properties of the latter are changed in real-time so as to make the force provided by the damper match the desired SH damping force as closely as possible. To this aim, two prototype magnetorheological dampers have been installed at the first level of the frame and remotely driven by a SH controller. The effectiveness of the control strategy is measured as response to reduction in terms of floor accelerations and interstory drift in respect to the uncontrolled configuration. Two different calibrations of the SH controller have been tested. The experimental results are deeply discussed in order to identify the optimal one and understand the motivations of its better performance.